Natural Immunomodulators: Promising Therapy for Disease Management - Muskan Altaf Tamboli,; Rutuja Ramdas Bhosale,; Naziya Ashpak Tamboli, (Indian Journal of Pharmacy & Drug Studies, 2024)
The immune system comprises a complex group of processes that provide defense against diverse pathogens. These defenses can be divided into innate and adaptive immunity, in which specific immune components converge to limit infections. We reviewed currently available experimental and clinical evidence to prove the efficiency, safety, and feasibility of immunomodulation in-vitro and in-vivo. We also reviewed the advantages and limitations of the described techniques. Despite its limitations, immunomodulation is considered as the therapy itself or as an adjunct with promising results and developing potential. Many plants and some phytoconstituents responsible for immunomodulation have been explained. The study also discusses biological screening methods for various plant drugs that focus on revealing the mechanism involved in immunomodulation. Nutraceuticals are essential food constituents that provide nutritional benefits as well as medicinal effects. The benefits of these foods are due to the presence of active compounds such as carotenoids, collagen hydrolysate, and dietary fibers.